Graphene and quantum electrodynamics - Gusynin, V.P. (Вопросы атомной науки и техники, 2013)
A single atomic layer of carbon, graphene, has the low-energy "relativistic- like" gapless quasiparticle excitations which in the continuum approximation are described by quantum electrodynamics in 2+1 dimensions. The Dirac- like character of charge carriers in graphene leads to several unique electronic properties which are important for applications in electronic devices. We study the gap opening in graphene following the ideas put forward by P. I. Fomin for investigation of chiral symmetry breaking and particle mass generation in quantum field theory. Одноатомний шар в углецю, графен, має низькоенергетичнi безщiлиннi квазiчастинковi збудження, якi в континуальному наближеннi описуються квантовою електродинамiкою в розмiрностi 2+1. Дiракiвський характер заряджених носiї в у графенi призводить до багатьох унiкальних електронних властивостей, що мають важливе значення для застосувань в електронних пристроях. Ми дослiджуємо вiдкриття щiлини в графенi, слiдуючи iдеям, запропонованим П.I.Фомiним для дослiдження порушення киральної симетрiїi генерацiї мас частинок у квантовiй теорiї поля. Одноатомный слой углерода, графен, обладает низкоэнергетическими безщелевыми квазичастичными возбуждениями, которые в континуальном приближении описываются квантовой электродинамикой в размерности 2+1. Дираковский характер заряженных носителей в графене приводит ко многим уникальным электронным свойствам, имеющим важное значение для применений в электронных устройствах. Мы исследуем открытие щели в графене, следуя идеям, предложенным П.И.Фоминым для исследования нарушения киральной симметриии генерации масс частиц в квантовой теории поля.